Biological Half-Life of Technetium-99m Ethambutol in Tuberculosis Patients: A Whole-Body Scan Perspective - Morgan Hanny Griselda Sinaga; Ryo Rachman Harade; Josua Timotius Manik (Jurnal Fisika, 2024)
The development of an etambutol radiopharmaceutical kit by PTNBR Batan aims to enhance the specificity of Mycobacterium Tuberculosis (MTb) imaging, the causative agent of tuberculosis. This research evaluates the distribution and biological half-life of Technetium-99m Etambutol radiopharmaceutical in the lungs, right kidney, left kidney, and bladder. This information is crucial for understanding the radiopharmaceutical's distribution within the body and improving the interpretation of whole-body etambutol scan results. The region of interest (ROI) technique was employed to delineate the areas of interest in the anterior and posterior images. The study sample consisted of 12 patients suspected of TB, with 5 females and 7 males aged 24 to 75 years. The results demonstrated that technetium-99m etambutol was distributed throughout the body with primary excretion routes through urine and feces. The highest activity was observed in the lungs, indicating the presence of tuberculosis infection. The longest biological half-life of technetium-99m etambutol was recorded in the left kidney (5.74 ± 1.42 hours) with a decay constant of 0.242 hour-1 and the right kidney (5.10 ± 1.89 hours) with a decay constant of 0.269 hour-1.